Selective growth of ZnTe on sapphire substrates using a SiO2 mask. Issue 11 (21st September 2016) - Nakasu, Taizo; Hattori, Shota; Sun, Wei‐Che; Kobayashi, Masakazu
Abstract : ZnTe/sapphire heterostructures have attracted attention for their suitable properties as a terahertz wave detector material. In this study, we focused on the selective growth of ZnTe on SiO2 ‐masked sapphire substrates by molecular beam epitaxy (MBE). When ZnTe was grown at a high temperature (=350 °C), low growth rate (≦ 0.3 μm h −1 ), and low J Te / J Zn flux ratio (≦ 0.83) compared with the conventional film growth conditions, the formation of ZnTe nuclei on the SiO2 mask was avoided. The Te flux intensity significantly affected the selectivity of ZnTe growth. The selective growth of ZnTe on sapphire was revealed to be limited by the desorption of Te adatoms from the SiO2 .